2015
DOI: 10.1080/00380768.2015.1054773
|View full text |Cite
|
Sign up to set email alerts
|

Bromine and iodine in Japanese soils determined with polarizing energy dispersive X-ray fluorescence spectrometry

Abstract: The bromine (Br) and iodine (I) status of Japanese soils was investigated by analyzing around 900 soil samples and related materials with polarizing energy dispersive X-ray fluorescence spectrometry (EDXRF). The samples consisted of the following five groups: (1) 468 soil samples collected from 70 sites in the mainland of Japan (mainland soils); (2) 139 agricultural soils collected nationwide; (3) 93 samples taken from the southwestern island (island soils); (4) 52 coastal marine sediments; and (5) 137 tsunami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Partly this may be due to the fact that concentrations of Br in soils and in terrestrial plants are usually low (Fuge, 1988;Birsin et al, 2010;Leri and Myneni, 2012;Yamasaki et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Partly this may be due to the fact that concentrations of Br in soils and in terrestrial plants are usually low (Fuge, 1988;Birsin et al, 2010;Leri and Myneni, 2012;Yamasaki et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Regardless of the specific function, it is strongly suggested that 127 I in the sediment is bound to organic materials. Previous studies have also reported that the majority of iodine in the seabed sediments and terrestrial soils was combined with organic matter [10][11][12][13][14][15]. If terrestrial organic iodine compounds existed and accounted for a significant part of the sedimentary iodine, the higher 129 I/ 127 I atom ratio in the sediment compared to that in the seawater may be caused by sedimentation of terrestrial organic iodine compounds.…”
Section: Resultsmentioning
confidence: 98%
“…The data for the lake is only available for 1997. The data for the lake surface (0-5 cm) sediments are from Ueda et al [8,14] before the cutting period. The 129 I/ 137 Cs activity ratios at St. 4 increased in 2007 and remained high after that year.…”
Section: Sampling Yearmentioning
confidence: 99%
“…Yamasaki et al . [ 24 ] also suggested that the geometric mean of Br is the highest in coastal marine sediments. Therefore, it is inferred that serum Br concentrations in horses pastured (Shizuoka-a) on green grass may have been influenced by the environment.…”
Section: Discussionmentioning
confidence: 99%